Determination of the Hansen solubility parameters with a novel optimization method. Issue 16 (24th December 2015) - Weng, Ming
ABSTRACT: The Hansen solubility parameters (HSPs) are useful for predicting solvent–solute affinity. In this study, the HSPs and the sphere radii ( Ro 's) of poly(ether sulfone), bitumen, and lignin were determined by a novel optimization method. A hybrid algorithm, which could locate multiple optima, was developed and used to solve optimization problems for maximizing the fitness ( F ) and minimizing both Ro and the numbers of good solvent and total outliers. For most selected samples, improved results with higher F and reduced Ro and number of outliers were obtained. The results clarify the correlations among three criteria for an optimal solubility sphere, namely, the smallest Ro, highest F, and lowest number of outliers. They can be satisfied simultaneously only when outliers are avoided; otherwise, a reduction in Ro decreases F but can retain the same outliers. Thereby, defining the solubility sphere as the one having the smallest Ro and the lowest number of outliers is more reasonable according to the physical significance in both cases. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43328. Abstract :